Granulomatous mediastinal adenopathy: can endoscopic ultrasound-guided fine-needle aspiration differentiate between tuberculosis and sarcoidosis? - Fritscher-Ravens, A.; Ghanbari, A.; Topalidis, T.; Pelling, M.; Kon, O. M.; Patel, K.; Arlt, A.; Bhowmik, A. (Endoscopy, 2011)
Background and study aims: Mediastinal lymphadenopathy may indicate diseases such as tuberculosis or sarcoidosis, and it is often difficult to establish a diagnosis when standard medical work-up is inconclusive. In this study we investigated the diagnostic yield of endoscopic ultrasound-guided fine-needle aspiration (EUS – FNA) in the differentiation between tuberculosis and sarcoidosis.Patients and methods: In this prospective study, 72 consecutive patients with mediastinal lymphadenopathy, negative endoscopic investigations including bronchoscopic procedures, and no radiological evidence of lung cancer or other malignancies on computed tomography were enrolled. EUS – FNA and subsequent cytology, microscopy for acid-fast bacilli, and culture were performed. At least 12 months’ follow-up including further investigations was included to exclude tuberculosis. Results: Adequate samples were obtained from 71/72 patients (36 male; mean age 50.2 years). No complications occurred. The final diagnosis included 30 cases of sarcoidosis, 28 of tuberculosis, four malignancies, one abscess, and nine benign lymphadenopathies. The size of lymph nodes on EUS varied from 0.5 cm to 4.2 cm. Tuberculosis nodes were significantly smaller than those in sarcoidosis. Unrelated nodes were significantly smaller than in either tuberculosis or sarcoidosis. The sensitivity, specificity, and positive and negative predictive values of EUS – FNA for tuberculosis were 86 %, 100 %, 100 %, and 91 %, respectively; those for sarcoidosis were 100 %, 93 %, 91 %, and 100 %, respectively. For culture of tuberculosis, they were 71 %, 100 %, 100 %, and 84 %, respectively. EUS – FNA led to a definite diagnosis in 64/72 cases (89 %) that had not been previously diagnosed by routine methods.Conclusion: EUS – FNA offers a high diagnostic yield for the differential diagnosis of tuberculosis and sarcoidosis that have not been diagnosed by conventional methods.